Intermittent prophylactic antibiotics for bronchiectasis - Spencer, Sally (Cochrane Database Syst Rev, 2019)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To evaluate the safety and efficacy of intermittent prophylactic antibiotics in the treatment of adults and children with bronchiectasis.